Variants of NAV3, a neuronal morphogenesis protein, cause intellectual disability, developmental delay, and microcephaly - Ghaffar, Amama; Akhter, Tehmeena; Strømme, Petter; Misceo, Doriana; Khan, Amjad; Frengen, Eirik; Umair, Muhammad; Isidor, Bertrand; Cogné, Benjamin; Khan, Asma A; Bruel, Ange-Line; Sorlin, Arthur; et al. (Communications biology, 2024)
Microtubule associated proteins (MAPs) are widely expressed in the central nervous system, and have established roles in cell proliferation, myelination, neurite formation, axon specification, outgrowth, dendrite, and synapse formation. We report eleven individuals from seven families harboring predicted pathogenic biallelic, de novo, and heterozygous variants in the NAV3 gene, which encodes the microtubule positive tip protein neuron navigator 3 (NAV3). All affected individuals have intellectual disability (ID), microcephaly, skeletal deformities, ocular anomalies, and behavioral issues. In mouse brain, Nav3 is expressed throughout the nervous system, with more prominent signatures in postmitotic, excitatory, inhibiting, and sensory neurons. When overexpressed in HEK293T and COS7 cells, pathogenic variants impaired NAV3 ability to stabilize microtubules. Further, knocking-down nav3 in zebrafish led to severe morphological defects, microcephaly, impaired neuronal growth, and behavioral impairment, which were rescued with co-injection of WT NAV3 mRNA and not by transcripts encoding the pathogenic variants. Our findings establish the role of NAV3 in neurodevelopmental disorders, and reveal its involvement in neuronal morphogenesis, and neuromuscular responses.
Keywords: vývojové poruchy u dětí; Chlorocebus aethiops; proteiny nervové tkáně; Humans; Microcephaly; Nerve Tissue Proteins; dítě; mikrocefalie; Child; Female; COS Cells; Developmental Disabilities; dánio pruhované; lidé; HEK293 Cells; zvířata; neurony; myši; mentální retardace; Mice; Cercopithecus aethiops; předškolní dítě; COS buňky; Intellectual Disability; Zebrafish; ženské pohlaví; Male; HEK293 buňky; proteiny asociované s mikrotubuly; Neurons; Animals; mužské pohlaví; Child, Preschool; Microtubule-Associated Proteins